Modos de viver e trabalhar: a questão da moradia no distrito de Perus, zona Oeste de São Paulo - Silva, Simone Borges da (2017)
The aim of this research was to understand the versions of adequate housing in the daily life of people that live and/or work in the district of Perus, in the municipality of São Paulo. The research is relevant due to the centrality of housing for obtaining other human rights, as established in international and national directives pertaining to dignified ways of living, especially with regards to people who live in areas that have been prone to environmental and housing interferences due to urban and industrial growth. The choice of Perus as a focus of research is justified by the recent densification of the resident population due to 1) environmental and social problems derived from the installation of a cement factory in the region; 2) the housing developments by the Housing Development Programs (CDHU) and 3) the informal occupation of an area called “Recanto”. In these three events, there has been an accelerated and disorganized urban growth with impact in the ways of living and working in the region. The research was based on a descriptive and analytic method. Snowball sampling was used to locate people that either lived in the region or had some connection with the district. For analysis of the interviews, Dialogical Maps, an analytic strategy developed at the Núcleo de Estudos sobre Práticas Discursivas no Cotidiano: direitos, risco e saúde (NUPRAD/PUC-SP), were used. It is hoped that the results might contribute to the improvement of the quality of life for those living in the District of Perus